Acoustic Parameters Giving the Angry Impression in Lampungnese Neutral Speech - Redika Cindra Reranta; Myrna Laksman Huntley (Masyarakat Linguistik Indonesia, 2022)
Misinterpretation of intonation can cause obstacles in communication or more severe problems. One case, for example, of misunderstanding intonation was that nonnative speakers often thought that Lampungnese neutral speech uttered by native speakers was angry speech. This research was conducted in order to carry out the acoustic factor behind the misunderstanding. This study applied the IPO approach with three main activities: speech production, speech acoustic analysis, and perceptual test experiments. The data were recordings of Lampungnese neutral speech. The utterance consisted of three sentence patterns, each of which was repeated four times by four native speakers. Furthermore, the data were compared to Indonesian neutral speech to find out the contrast between them. The contrasts were considered according to the acoustic parameter which gave an angry impression in Lampungnese neutral speech. Results of analysis showed that neutral Indonesian and Lampungnese neutral speech were differentiated by pitch; Lampungnese pitch is higher and its contour pattern resembles angry speech patterns. Furthermore, experimental results showed that different pitch height and contour pattern lead to the perception of nonLampung speakers considering Lampungnese neutral speech as angry speech.